Performance and intestinal mucosa development of broiler chickens fed diets containing Saccharomyces cerevisiae cell wall - Santin, E.; Maiorka, A.; Grecco, M .; Macari, Marcos [UNESP]; Sanchez, J. C.; Okada, T. M.; Myasaka, A. M. (Poultry Science Assoc Inc, 2001)
Use of antibiotics as an additive in poultry diets to improve growth has been discussed in relation to bacterial resistance and the development of new products and management practices. This study was carried out to test the efficacy of a new substance (Saccharomyces cereviside cell walls, var. Calsberg- SCCW) obtained from the brewery industry, added (at 0.1 and 0.2%) to broiler chicken diets (based on corn and soybean meal), on performance and intestinal mucosa development. In Experiment 1 (carried out in litter-floor pens) the results revealed higher body weight gain,for the total experimental period and higher villus height at 7 d of age for the birds fed 0.2%,SCCW. In a field test using 44,000 broilers that,received feed containing 0.2% SCCW,. The results also showed higher body weight gain and better feed conversion for SCCW-supplemented birds. The present findings show that SCCW improved body weight gain in broiler chickens and that this effect can be attributed to the trophic effect of this product on the intestinal mucosa, because it increases villus height, particularly during the first 7. d of a chicken's life.
Keywords: broiler; crypt depth; Mucosa intestinal; Saccharomyces cerevisiae cell wall; villus height